Tangent Host: An Uneasy Partnership. (October 2019) - Ensign, Prescott C.; Robinson, Nicholas P.
Tangent Host, a Canadian-based website services provider, was established in 2014 as a general partnership by two personal and professional friends. Each had a 50% ownership stake in profits and workload. In 2016, it had total revenue of US$121, 440, divided evenly between web design (100 clients) and web hosting (375 clients). As a start-up, Tangent had taken advantage of growth opportunities and had overcome a number of operational challenges. By 2017, there were mounting unresolved issues: tension between partners, concerns with uncollected receivables, technical performance, and future direction. One of the partners seemed to be less committed to the partnership, shifting interest and time to other activities that generated personal not partnership income. The case provides thought-provoking issues confronted by a new venture and partnership: friction between partners, customer relations, service performance, increasing revenue, scaling a business, making strategic choices, and conflict resolution.